2016
DOI: 10.1158/0008-5472.can-15-2860
|View full text |Cite
|
Sign up to set email alerts
|

FOXD1–ALDH1A3 Signaling Is a Determinant for the Self-Renewal and Tumorigenicity of Mesenchymal Glioma Stem Cells

Abstract: Glioma stem-like cells (GSC) with tumor initiating activity orchestrate the cellular hierarchy in glioblastoma (GBM) and engender therapeutic resistance. Recent work has divided GSC into two subtypes with a mesenchymal (MES) GSC population as the more malignant subtype. In this study, we identify the FOXD1-ALDH1A3 signaling axis as a determinant of the MES GSC phenotype. The transcription factor FOXD1 is expressed predominantly in patient-derived cultures enriched with MES, but not with the proneural (PN) GSC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
148
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 43 publications
3
148
0
1
Order By: Relevance
“…Furthermore, we revealed that a higher expression level of FOXD1 was associated with malignant behavior and poorer prognosis of NSCLC patients. It is worth mentioning that FOXD1 is after all a transcription factor so nuclear localization would be expected, but FOXD1 was mainly in cytoplasm, which was previously reported [8]. However, we don't found that high levels of FOXD1 expression were significantly associated with these clinicopathological findings, including the presence of squamous cell carcinoma, male gender and history of heavy smoking.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Furthermore, we revealed that a higher expression level of FOXD1 was associated with malignant behavior and poorer prognosis of NSCLC patients. It is worth mentioning that FOXD1 is after all a transcription factor so nuclear localization would be expected, but FOXD1 was mainly in cytoplasm, which was previously reported [8]. However, we don't found that high levels of FOXD1 expression were significantly associated with these clinicopathological findings, including the presence of squamous cell carcinoma, male gender and history of heavy smoking.…”
Section: Discussionmentioning
confidence: 49%
“…Thus, the dysregulation of FOX genes is also observed in a variety of cancerspage5. The FOXD1 gene is located on chromosome 5q12 and is involved in a wide array of biological processes, including proliferation, invasion and tumorigenesis [5,7,8]. A previous study used microarray datasets from 90 lung cancer specimens to analyze the levels of FOXD1 mRNA and found that the aberrant FOXD1 mRNA was correlated with NSCLC patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the feasibility of local delivery to BTICs directly in the core of xenografts in mice, we opted to encapsulate combinations of siRNAs in 7C1 LPNPs targeting the four TFs concurrently. Because other circuits are responsible for maintaining the stem celllike phenotypes in other GBM subgroups listed in The Cancer Gene Atlas (TCGA), and because additional genetic/epigenetic circuits are being identified (25)(26)(27)(28), the current choice of RNAi therapeutic targets is not expected to apply to all GBM subtypes. The primary purpose of our work was to establish a proof-ofprinciple approach and to demonstrate that tumorigenesis can be antagonized using this vehicle and delivery strategy.…”
mentioning
confidence: 99%